2005
DOI: 10.1109/lmwc.2005.859944
|View full text |Cite
|
Sign up to set email alerts
|

A wideband array of stacked patch antennas using embedded air cavities in LTCC

Abstract: An embedded air cavity in low temperature cofired ceramics (LTCC) is used to achieve a wideband response with stacked patch antennas. A single LTCC stacked patch antenna achieves a gain of better than 5 dBi over an 18% bandwidth with a good impedance match. A 2 2 element array of stacked patches is also realized, and achieves a 3-dB gain bandwidth from 25 to 30 GHz with a maximum gain of 11.1 dBi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 1 publication
0
27
0
Order By: Relevance
“…The antenna we propose avoids use of complex (and expensive for manufacturing) previously investigated techniques such as air-cavity or punching holes and demonstrates a larger than other LTCC antennas [5][6][7] relative bandwidth. The antenna is based on an ASP antenna.…”
Section: A) Antenna Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The antenna we propose avoids use of complex (and expensive for manufacturing) previously investigated techniques such as air-cavity or punching holes and demonstrates a larger than other LTCC antennas [5][6][7] relative bandwidth. The antenna is based on an ASP antenna.…”
Section: A) Antenna Geometrymentioning
confidence: 99%
“…However, these approaches will complicate the manufacturing of the antenna, lower the yield rate, and increase cost. The operational bandwidth of LTCC antennas reported in literature is typically below 18% [6,8].This paper presents a novel differentially fed UWB antenna for CWD imaging radar. The antenna should be manufactured using the LTCC technology to be ready for integration with 60 GHz MMICs for UWB front-end.…”
mentioning
confidence: 99%
“…49 This technique has also been used to create embedded air cavities, which serve as an ideal dielectric in an LTCC stacked patch antenna (with dimensions of 11 mm × 6 mm × 0.392 mm). 50 Instead of using adhesive tapes, organic liquids, such as natural honey, glucose, and polyester resins, can be used as gluing agents to bond the LTCC tapes at room temperature and under a pressure of 2.5 or 5 MPa. 51 The gluing agents are removed during the debinding stage.…”
Section: Lamination Using Adhesive Materialsmentioning
confidence: 99%
“…The observed saggings after sintering for suspended threelayers and six-layers self-constrained laminates were less than −120 m. These results indicated that supporting medium is not necessary during sintering for the fabrication of relatively large embedded structures (with width ranges 15-25 mm) made of self-constrained LTCC material. The fabrication of large embedded cavity is practically useful in realizing embedded air cavity for stacked patch antennas 18,19 and pressure sensor. 13 …”
Section: Deformation Of Suspended Ltcc Laminate During Sinteringmentioning
confidence: 99%